Chemical Composition and Nutraceutical Potential of Indian Borage (Plectranthus amboinicus) Stem Extract. (27th August 2013) - Bhatt, Praveena; Joseph, Gilbert Stanley; Negi, Pradeep Singh; Varadaraj, Mandyam Chakravarthy
Abstract : The stem of Indian borage ( Plectranthus amboinicus ) was found to be an antioxidant rich fraction as evaluated by in vitro models such as DPPH free radical scavenging, reducing power assay, superoxide anion radical scavenging, and total antioxidant capacity. The extract also exhibited antiplatelet aggregation ability, antibacterial activity, and antiproliferative effect against cancer cell lines: Caco-2, HCT-15, and MCF-7. Phytochemical evaluation of the extract revealed the occurrence of total phenolics (49.91 mg GAE/g extract), total flavonoids (26.6 mg RE/g extract), and condensed tannins (0.7 mg TAE/g extract). Among the major phenolics, rosmarinic acid (6.160 mg/g extract) was predominant, followed by caffeic acid (0.770 mg/g extract), rutin (0.324 mg/g extract), gallic acid (0.260 mg/g extract), quercetin (0.15 mg/g extract), and p -coumaric acid (0.104 mg/g extract). The appreciable biological activity and presence of biomolecules in the methanolic extract of stem indicate its potential application as functional food ingredients and nutraceuticals.